Treating tobacco dependence in older adults: a survey of primary care clinicians’ knowledge, attitudes, and practice - Huddlestone, Lisa; Walker, Gemma M.; Hussain-Mills, Robana; Ratschen, Elena (BioMed Central, 2015)
BACKGROUND: The benefits of smoking cessation among older people are well documented. Despite this, evidence suggests that older smokers are rarely engaged in smoking cessation efforts, and that existing tobacco dependence treatments require further tailoring to the specific needs of older smokers. This study assesses the knowledge, attitudes, and clinical practice of primary care clinicians in relation to addressing tobacco dependence among older people.